Criterios para el otorgamiento de la bonificación diferencial en el Régimen Laboral de la Actividad Pública - Enciso Rivera, Wilfredo (Revista de Derecho, 2019)
The Civil Service Laws in Peru, regulates a remunerative concept called “BonificaciónDiferencial” (Differential Bonus), designed for being paid to civil servants, butonly when they hold a special kind of managerial positions called “cargos de responsabilidaddirectiva”.This article aims to bring up for discussion the criteria of interpretation and applicationof such rules by administrative and judicial authorities, because of the way theyunderstand the very concept of “cargo de responsabilidad directiva”, which is thekey concept to determinate if the Bonus should be paid or not. In order to do thisanalysis, certain technical aspects of the Peruvian Civil Service regulations will bereviewed.
Keywords: Peruvian Civil Service; Peruvian Public Management